2017
DOI: 10.3892/mmr.2017.6124
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of microarray datasets to identify Parkinson's disease-associated pathways and genes

Abstract: In order to investigate commonly disturbed genes and pathways in various brain regions of patients with Parkinson's disease (PD), microarray datasets from previous studies were collected and systematically analyzed. Different normalization methods were applied to microarray datasets from different platforms. A strategy combining gene co-expression networks and clinical information was adopted, using weighted gene co-expression network analysis (WGCNA) to screen for commonly disturbed genes in different brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Given that the biological significance of these modules might be related to the potential clinical manifestations, we performed Cox regression analysis for each module to determine their survival outcomes [ 1 , 11 , 39 , 40 ]. Poor outcomes were found for the high expression group of the salmon module, which was consistent with previous results indicating that the high expression of the salmon module might represent a higher pathological stage and the T stage [ 2 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that the biological significance of these modules might be related to the potential clinical manifestations, we performed Cox regression analysis for each module to determine their survival outcomes [ 1 , 11 , 39 , 40 ]. Poor outcomes were found for the high expression group of the salmon module, which was consistent with previous results indicating that the high expression of the salmon module might represent a higher pathological stage and the T stage [ 2 ].…”
Section: Discussionsupporting
confidence: 90%
“…Accurate staging of rectal cancer (RC) is essential for carrying out precise therapies that increase the survival rate of patients [ 1 ]. Previous studies have found no differences in specific clinicopathological risk factors between patients with a high or low risk of RC progression [ 2 ]. Recent technological breakthroughs in genome-wide sequencing have shed new insights on deregulated mRNAs that have been identified and characterized in the past few years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment of AD genes in cancer-related pathways reveal that some degrees of overlap in the potential pathogenesis of AD and cancers. Genes associated with neurodegenerative diseases, such as PD, are often abnormally expressed in cancers and also involved in cell cycle maintenance (12). Therefore, genes involved in cancers may be potential therapeutic targets for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) is a bioinformatic analysis method that can determine the bridge between sample characteristics and gene expression changes (9). Previous studies had reported that WGCNA could be utilized to analyze the relationships between genes and relationships between gene expressions and clinical characteristics of neurodegenerative diseases (10)(11)(12). Six genes were recognized to be involved in the pathological changes of AD (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation